Nailfold capillaroscopy and retinal findings in patients with systemic sclerosis: Is there an association? - Deepak Jakhar; Chander Grover; Archana Singal; G K Das (Wolters Kluwer Medknow Publications, 2020)
Introduction: Systemic sclerosis (SSc) is characterized by fibrosis and intimal proliferation of cutaneous and visceral small vessels. These architectural abnormalities can be visualized with nailfold capillaroscopy (NFC); the changes being quite characteristic. At the same time, morphological alterations in retinal vascular bed are expected but sparsely described. Aim: We aimed to characterize the frequency and type of retinal microvascular changes in patients with SSc and to analyze any association with NFC changes. Patients and Methods: With institutional ethical committee approval, we recruited 45 consecutive patients with SSc (diagnosed based on American College of Rheumatology and European League against Rheumatism [ACR/EULAR-2013] criteria). NFC was done for all of them with a Universal Serial Bus (USB) dermatoscope; additionally, fundoscopy, fundus photography, and optical coherence tomography (OCT) were analyzed. Disease characteristics in patients with and without retinal disease were compared. Results: Among the 45 SSc patients, 12 (26.67%) had limited cutaneous SSc (lSSc) while 33 (73.33%) had diffuse cutaneous disease (dSSc). Retinal microvascular changes seen as mild arteriolar alteration and arteriovenous crossing changes were recorded in 13 patients (28.89%); mostly in those with dSSc (12/13). The NFC architectural changes were more severe in patients with retinal disease, though the difference was not statistically significant. Conclusion: Patients with SSc can often have retinal microvascular abnormalities commensurate with the vascular changes characteristic of SSc. The severity of retinal changes correlates with changes in NFC. NFC, which is now an essential tool for the management of SSc, could be a surrogate marker for retinal involvement in these patients.